Application of Sensor Networks in a Smart Apartment - Salehi-Abari, Omid; Alaca, Furkan; Green, James R.; Goubran, Rafik (CMBES Proceedings, 2010)
Home-based health monitoring systems provide an opportunity to enhance the quality of life for older adults by allowing them to live independently and improving doctor-patient efficiency. These systems are more cost effective than constant medical supervision in an institutional setting and will help in reducing the load on the healthcare system. In this paper we propose a number of non-invasive applications of low-cost and low-powered wireless sensor networks aimed to monitor various aspects of a user’s health, daily activities, and environment. Data fusion techniques are used to combine measurements from simple temperature, humidity, and light sensors to ultimately aid in health monitoring and detecting medical emergencies. We propose algorithms which can be used to help detect falls in the shower, monitor exposure to natural sunlight, and collect data on day-to-day activities such as bathroom use. The information collected can then be forwarded to health care professionals or emergency contacts. Although this is a pilot study, we aim to deploy the final sensor network and data fusion system in an instrumented Smart Apartment as part of the TAFETA initiative. *O. Salehi-Abari and F. Alaca contributed equally to this work